A study of the specific IgM antibody response in Mycoplasma pneumoniae infection in man. - Chamberlain, P. (Cambridge University Press, 1983)
Sera from 96 patients with Mycoplasma pneumoniae infection were examined for specific IgM antibody. The complement fixation test was used to measure the IgM after separation by ultracentrifugation through sucrose density gradients. Of patients under the age of 20 years 78% displayed positive specific IgM titres. In older patients only 34% were IgM positive. The specific IgM remained detectable, but at decreasing levels, during the follow-up period of 5 months. This diagnostic technique appears to be of value in children and young adults experiencing primary infection with M. pneumoniae.